2017
DOI: 10.1038/srep41996
|View full text |Cite
|
Sign up to set email alerts
|

Structural insights into human angiogenin variants implicated in Parkinson’s disease and Amyotrophic Lateral Sclerosis

Abstract: Mutations in Angiogenin (ANG), a member of the Ribonuclease A superfamily (also known as RNase 5) are known to be associated with Amyotrophic Lateral Sclerosis (ALS, motor neurone disease) (sporadic and familial) and Parkinson’s Disease (PD). In our previous studies we have shown that ANG is expressed in neurons during neuro-ectodermal differentiation, and that it has both neurotrophic and neuroprotective functions. In addition, in an extensive study on selective ANG-ALS variants we correlated the structural c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 68 publications
2
34
0
Order By: Relevance
“…Amyotrophic lateral sclerosis (ALS) overlaps clinically and pathologically with other neurodegenerative diseases. 1 5 Family members of patients with ALS have also been reported to have increased risks of dementia and Parkinson disease (PD), 6 , 7 further supporting the hypothesis of a shared etiopathogenesis between ALS and other neurodegenerative diseases. 6 , 8 , 9 Increased risk of psychiatric disorders has been suggested among patients with ALS in some but not all studies 10 12 and little is known for the risk of psychiatric disorders among families of patients with ALS.…”
mentioning
confidence: 93%
“…Amyotrophic lateral sclerosis (ALS) overlaps clinically and pathologically with other neurodegenerative diseases. 1 5 Family members of patients with ALS have also been reported to have increased risks of dementia and Parkinson disease (PD), 6 , 7 further supporting the hypothesis of a shared etiopathogenesis between ALS and other neurodegenerative diseases. 6 , 8 , 9 Increased risk of psychiatric disorders has been suggested among patients with ALS in some but not all studies 10 12 and little is known for the risk of psychiatric disorders among families of patients with ALS.…”
mentioning
confidence: 93%
“…According to previously reported molecular simulation results of the V103I variant structure, a hydrogen bond interaction network connecting from I103 to H114 was proposed (Padhi et al., ). Enzyme activity assays showed that the V103I mutant retains 54.1% of enzymatic activity toward tRNA (Bradshaw et al., ). Observing SASA values of the V103I mutant, it is predicted that the nuclear translocation activity is also impaired (Padhi et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…According to the ribonucleolytic activity assay, the R33W mutant protein retained 57.4% of catalytic activity of the wild‐type protein. Previous studies described that the reported disease‐causing ANG mutations—except variant R121C—show a reduced level of catalytic activity in a range of 0%–95% compared with the wild‐type ANG (Bradshaw et al., ; Padhi et al., ; Wu et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of the vicious cycle of abnormal placental development in intrauterine growth restriction, placental mesenchymal stromal cells lose angiogenic potential while acquiring adipogenic capacity which is coincided with a metabolic shift from aerobic to anaerobic state [71]. It seems that [11] Angiopoietin-1 +/+ Activates TEK/TIE2 receptor; promotes angiogenic processes, endothelial cell survival, migration, proliferation, and stabilization; and during embryogenesis has a role in heart development [12] Angiopoietin-2 +/− Binds to TEK/TIE2, in the presence of VEGF and Ang-2 and promotes neovascularization [13,14] Angiopoietin-4 +/+ Binds to TEK/TIE2, modulating ANGPT1 signaling, can induce tyrosine phosphorylation of TEK/TIE2, and promotes endothelial cell survival, migration, and angiogenesis [15] Amphiregulin +/− An EGF-like ligand that binds to the EGFR, enhanced lymphangiogenesis, and stimulates the growth of normal epithelial cells [16] Artemin +/− Binds for the GFR-alpha-3-RET and GFR-alpha-1-RET receptor and promotes angiogenesis [17] Tissue factor +/− Stimulates PDGF receptor signaling pathway, angiogenesis, endothelial cell migration, chemotaxis and proliferation, and coagulation factor III/CD142; improves transcription of VEGF; and reduces transcription of the thrombospondins [18] CXCL16 +/+ Encourages a chemotactic response, pro-angiogenic [19] DPPIV +/− A membrane-bound oligopeptidase acting on and modulating the pro-angiogenic chemokine CXCL12 [20] Epidermal growth factor +/− Encourages the growth of epithelial tissues, is anti-apoptotic, induces lymphangiogenesis, and improves MSC survival [21] EG-VEGF +/− Also called Prokineticin 1. Binds to PROKR1 and PROKR2, pro-angiogenic [22] Endothelin-1 +/+ Derived from the endothelium with vasoconstrictor and angiogenic effects, prolymphoangiogenic [23] Endoglin +/− Also called CD 105.…”
Section: Introductionmentioning
confidence: 99%